2023
DOI: 10.1038/s41388-022-02585-3
|View full text |Cite|
|
Sign up to set email alerts
|

Alpelisib and fulvestrant in PIK3CA-mutated hormone receptor-positive HER2-negative advanced breast cancer included in the French early access program

Abstract: BackgroundSOLAR-1 and BYLIEVE trials documented the e cacy of the PI3K-inhibitor alpelisib in pre-treated PIK3CAmutant, hormone receptor-positive, HER2-negative (HR+/HER2-) advanced breast cancer (ABC) patients.We report here real-life data of patients prospectively registered in the French alpelisib early access program (EAP). Patients and methods:The French EAP was opened to PIK3CA-mutant HR+/HER2-ABC patients treated with alpelisib and fulvestrant, managed per standard of care. Primary endpoint was PFS by l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…This median PFS is apparently shorter than that reported in the PrE0102 and MANTA trials, which included patients not pre-treated with CDK4/6i [ 9 , 10 ]. A similar shortening of second line PFS in CDK4/6i pretreated patients was previously observed with the fulvestrant-alpelisib combination, with median PFS of 11.0 months when given to CDK4/6i-naïve (SOLAR-1 trial [ 17 ]) versus 7.3 (BYLieve trial [ 18 ]) and 5.3 (French early access program [ 19 ]) months in CDK4/6i-pretreated mBC patients. In the post CDK4/6i setting, few retrospective studies have reported short-lived efficacy of everolimus-based combination (with exemestane or fulvestrant) : median PFS was 4.9 months in N = 12 patients [ 20 ], 4.2 months in N = 41 patients [ 21 ] and 3.8 months in N = 79 patients [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
“…This median PFS is apparently shorter than that reported in the PrE0102 and MANTA trials, which included patients not pre-treated with CDK4/6i [ 9 , 10 ]. A similar shortening of second line PFS in CDK4/6i pretreated patients was previously observed with the fulvestrant-alpelisib combination, with median PFS of 11.0 months when given to CDK4/6i-naïve (SOLAR-1 trial [ 17 ]) versus 7.3 (BYLieve trial [ 18 ]) and 5.3 (French early access program [ 19 ]) months in CDK4/6i-pretreated mBC patients. In the post CDK4/6i setting, few retrospective studies have reported short-lived efficacy of everolimus-based combination (with exemestane or fulvestrant) : median PFS was 4.9 months in N = 12 patients [ 20 ], 4.2 months in N = 41 patients [ 21 ] and 3.8 months in N = 79 patients [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
“…Recently, PIK3CA mutations have reached level 1 evidence to predict the benefit of alpelisib, an alpha-specific inhibitor of PI3K, in combination with fulvestrant in patients with advanced hormone receptor-positive/HER2-negative breast cancer previously treated with endocrine therapy, highlighting the usefulness of determining these affectations in oncological practice [ 16 , 17 , 18 , 19 ]. Additionally, in the context of hormone receptor-positive metastatic breast cancer, interactions in the estrogen receptor 1 ( ESR1 ) gene are a frequent cause of acquired resistance to estrogen deprivation due to aromatase inhibition [ 20 ]. The prevalence of ESR1 in primary mammary tumors is approximately 3%, however, in the metastatic setting, it is 13.6% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the context of hormone receptor-positive metastatic breast cancer, interactions in the estrogen receptor 1 ( ESR1 ) gene are a frequent cause of acquired resistance to estrogen deprivation due to aromatase inhibition [ 20 ]. The prevalence of ESR1 in primary mammary tumors is approximately 3%, however, in the metastatic setting, it is 13.6% [ 20 ]. This ESR1 difference between primary and metastatic tumors suggests that ESR1 mutation emerges during metastasis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K/AKT signaling is an important target for breast cancer treatment, and mutations in these pathways have been related to aggressive tumor behavior and treatment resistance ( 44 ). Prospective research has proven that the use of the PI3K inhibitor alpelisib can bring clinical benefits to patients with breast cancer, and has been approved for the targeted treatment of breast cancer ( 45 ). Therefore, circPRKCI is expected to become a potential therapeutic target for breast cancer.…”
Section: Roles Of Circprkci In Various Malignant Tumorsmentioning
confidence: 99%